Osteoarticular Infection in Three Young Thoroughbred Horses Caused by a Novel Gram Negative Cocco-Bacillus. (19th January 2020) - Hudson, Bernard J.; Chicken, Catherine; Blishen, Anna; Todhunter, Kristen H.; Begg, Angela P.; Chan, Leonie; Karagiannis, Thomas; Raymond, Benjamin; Bogema, Daniel; Adkins, Angus R.; O'Sullivan, Christopher B.; O'Rourke, Brendon A.; et al.
Abstract : We describe three cases of osteoarticular infection (OAI) in young thoroughbred horses in which the causative organism was identified by MALDI-TOF as Kingella species . The pattern of OAI resembled that reported with Kingella infection in humans. Analysis by 16S rRNA PCR enabled construction of a phylogenetic tree that placed the isolates closer to Simonsiella and Alysiella species, rather than Kingella species . Average nucleotide identity (ANI) comparison between the new isolate and Kingella kingae and Alysiella crassa however revealed low probability that the new isolate belonged to either of these species. This preliminary analysis suggests the organism isolated is a previously unrecognised species.